Aestheticism in Ṣūfism: تصوف میں جمالیات کا تصور (Al-Mithaq ( Research Journal of Islamic Theology), 2023)
The Ṣūfī finds his purpose in every form of beauty, he embraces this aesthetic world in nature's beautiful sights, beautiful faces, waterfalls, colors, lights and enchanting sounds, which he has to explore and feel. The main teaching of the Ṣūfī is to look at or contemplate the components, creation and creation of beauty in order to capture the manifestation (Ḥasan Muṭlaq) of the real essence of beauty. In this way, a person will reach this great world of aesthetics, where the original source of beauty and beuaty in its totality encompass. The life that will be spent under the influence of this beauty will have the pleasures from which a person will never want to exit and will always prefer to stay in such beautiful and blissful world of aesthetics. This paper delves into the intricate relationship between aesthetics and spirituality within the context of Ṣūfism, the mystical branch of Islam. Drawing upon a rich tapestry of Ṣūfī literature, poetry, and practices, it examines how the pursuit of beauty serves as a central tenet in the spiritual journey of Ṣūfī practitioners. The paper explores various aspects of Ṣūfī aesthetics, including the symbolism of art and architecture, the use of music and poetry as vehicles for spiritual elevation, and the cultivation of inner beauty through mystical practices. Furthermore, it investigates how Sufi aesthetics emphasize the importance of love, harmony, and unity as fundamental principles underlying the universe's beauty.